2020
DOI: 10.1590/1678-9865202033e190143
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction since lactation has reduced anxiety in adult Wistar rats

Abstract: Objective To evaluate the effects of macronutrients (protein, carbohydrate and/or lipid) in the diet of young adult (72 days) and adult (182 days) Wistar rats treated ad libitum and with 30% restriction from birth on anxiety in the elevated plus-maze. Methods We used 238 rats treated from birth, composing the groups: Control, Protein, Carbohydrate, Lipid, Carbohydrate and Lipid, Control Restriction, Protein Restriction, Carbohydrate Restriction, Lipid Restriction and Carbohydrate and Lipid Restriction. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The ratio of entries (considered as the animal inserting all the four paws) in each arm (closed or open) and the time spent in them were evaluated ( Teixeira et al, 2020 ). In addition, to analyze the risk assessment of animal, the frequency of head-dipping (the head flexes below the edge of the open arms), rearing (frequency with which the animal stands on its hind legs), and grooming (frequency of time which the animal spent licking or scratching itself while stationary) was recorded ( Plescia et al, 2015 ; Guedine et al, 2018 ; Riul and Almeida, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of entries (considered as the animal inserting all the four paws) in each arm (closed or open) and the time spent in them were evaluated ( Teixeira et al, 2020 ). In addition, to analyze the risk assessment of animal, the frequency of head-dipping (the head flexes below the edge of the open arms), rearing (frequency with which the animal stands on its hind legs), and grooming (frequency of time which the animal spent licking or scratching itself while stationary) was recorded ( Plescia et al, 2015 ; Guedine et al, 2018 ; Riul and Almeida, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, within the context of our own study, the hunger state dependency control experiment showed, despite being satiated (indicated by an equivalent increase in trial omissions in both groups), decision making was unaltered in all rats (indicated by the null effect of the feeding schedule on choices), and as such, the maladaptive decision-making phenotype reported here is not due to hunger-state dependency. Importantly, food-restricting rats to 80% of their ad libitum weight does not induce behavioral differences relative to controls ( Heiderstadt et al, 2000 ) but it can improve behavior ( Bruce‐Keller et al, 1999 ; Chowdhury et al, 2021 ; Kenny et al, 2014 ; Orsini et al, 2004 ; Parikh et al, 2016 ; Riul and Almeida, 2020 ; Stewart et al, 1989 ) and enhance resistance to excitotoxin-induced degeneration ( Bruce‐Keller et al, 1999 ). Therefore, we do not believe the degree of food restriction had an impairing effect on the TgAD rats, and it is possible this modest food restriction protocol could have prevented more severe impairments.…”
Section: Discussionmentioning
confidence: 99%
“…At the end filming for each animal, the maze was cleaned using 70% alcohol. Experienced observers evaluated: entries in the open arms at least one time (Lordi et al 2000); the frequency and duration of entries (when the animal entered with four legs) in each arm (closed or open); and frequency of head-dipping and false entries (Riul and Almeida, 2020).…”
Section: Elevated Plus Maze (Epm) Testmentioning
confidence: 99%